Kenya Media, Internet & Telecommunications Complete Profile : This All-Inclusive Profile Includes All Three of Our Communications Reports. - Press, World Trade (World Trade Press, 2010)
Get all three comprehensive reports bundled into one for a complete media and communications profile of Kenya. An excellent source of practical information, this profile offers an extensive dialing guide with city codes, a listing of ISPs and Internet cafes, profiles of the major media outlets (with contact info!) and more.